Integrated analysis of intestinal microbiota and metabolomic reveals that decapod iridescent virus 1 (DIV1) infection induces secondary bacterial infection and metabolic reprogramming in Marsupenaeus japonicus - He, Zihao; Zhong, Yunqi; Liao, Minze; Dai, Linxin; Wang, Yue; Zhang, Shuang; Sun, Chengbo (Frontiers in Immunology, 2022)
In recent years, with global warming and increasing marine pollution, some novel marine viruses have become widespread in the aquaculture industry, causing huge losses to the aquaculture industry. Decapod iridescent virus 1 (DIV1) is one of the newly discovered marine viruses that has been reported to be detected in a variety of farmed crustacean and wild populations. Several previous studies have found that DIV1 can induce Warburg effect-related gene expression. In this study, the effects of DIV1 infection on intestinal health of shrimp were further explored from the aspects of histological, enzymatic activities, microorganisms and metabolites using Marsupenaeus japonicus as the object of study. The results showed that obvious injury in the intestinal mucosa was observed after DIV1 infection, the oxidative and antioxidant capacity of the shrimp intestine was unbalanced, the activity of lysozyme was decreased, and the activities of digestive enzymes were disordered, and secondary bacterial infection was caused. Furthermore, the increased abundance of harmful bacteria, such as Photobacterium and Vibrio, may synergized with DIV1 to promote the Warburg effect and induce metabolic reprogramming, thereby providing material and energy for DIV1 replication. This study is the first to report the changes of intestinal microbiota and metabolites of M. japonicus under DIV1 infection, demonstrating that DIV1 can induce secondary bacterial infection and metabolic reprogramming. Several bacteria and metabolites highly associated with DIV1 infection were screened, which may be leveraged for diagnosis of pathogenic infections or incorporated as exogenous metabolites to enhance immune response.